The role of defects and excess surface charges at finite temperature for optimizing oxide photoabsorbers. Issue 12 (December 2018) - Gerosa, Matteo; Gygi, Francois; Govoni, Marco; Galli, Giulia
Abstract Computational screening of materials for solar to fuel conversion technologies has mostly focused on bulk properties, thus neglecting the structure and chemistry of surfaces and interfaces with water. We report a finite temperature study of WO3, a promising anode for photoelectrochemical cells, carried out using first-principles molecular dynamics simulations coupled with many-body perturbation theory. We identified three major factors determining the chemical reactivity of the material interfaced with water: the presence of surface defects, the dynamics of excess charge at the surface, and finite temperature fluctuations of the surface electronic orbitals. These general descriptors are essential for the understanding and prediction of optimal oxide photoabsorbers for water oxidation. Computational screening of materials for solar to fuel conversion technologies has mostly focused on bulk properties. A finite temperature study of WO3 now clarifies the role of defects and excess surface charges for optimizing oxide photoabsorbers.